A thermo-hydraulic characteristics investigation in corrugated plate heat exchanger. (February 2019) - Alzahran, Salman; Islam, Mohammad; Saha, Suvash
Abstract: The amount of heat transfer from plate heat exchanger (PHE) is much higher compared with other types of conventional heat exchangers due to the high surface area of each plate. This study aims to investigate the heat transfer characteristics in a commercial corrugated PHE for sinusoidal corrugation type. A computational fluid dynamics (CFD) has been used to simulate the fluid flow inside the PHE for 1-1 single (water-water) and two (air-water) phase flow, counter arrangement. An advanced meshing technique has been used to generate the mesh for the PHE and a proper grid refinement test has been performed for the generated mesh. The overall investigation has been conducted for 60°/60° chevron angle plate (β) for a wide range of Re (500 ≤ Re ≤3000) and Prandtl number (Pr) (0.72 ≤ Pr ≤ 7.5). The result is validated with the benchmark experimental data. The impact of Reynolds and Pr has been investigated. The CFD results illustrate that the Nusselt number (Nu) increases with increasing of Reynolds number, while f decreasing with increasing of Re. The effect of Pr on Nusselt number and isothermal friction factor is presented. The corresponding correlations of Nu and f are developed from the CFD results